Saturation Oxygenation Pressure Index: A Novel Non-invasive Approach for Evaluating Pulmonary Disease Severity in Neonates on Non Invasive Ventilation - Swetha Naikodi; AS Jagadish; R Premalatha; B Ravichander (Indian Journal of Neonatal Medicine and Research)
Introduction: Pulmonary disease poses a significant health challenge for neonates, necessitating precise assessment for effective management. Continuous distending pressure is crucial for achieving adequate Functional Residual Capacity (FRC) in these patients. Changes in distending pressure requirements, Fraction of Inspired Oxygen (FiO2), or both, indicate variations in disease severity. An integrated tool that incorporates these parameters would facilitate an objective evaluation of disease severity. The Saturation Oxygenation Pressure Index (SOPI) tool effectively scores and quantifies severity based on factors relevant to neonates receiving Non Invasive Positive Pressure Ventilation (NIPPV) or Continuous Positive Airway Pressure (CPAP). Aim: To determine the correlation between SOPI and the Alveolar-Arterial Oxygen Gradient (AaDO2). Additionally, it seeks to establish the cut-off values of SOPI that correspond to AaDO2 values of 70 (mild), 85 (moderate), and 100 (severe) respiratory diseases, respectively. Materials and Methods: This cross-sectional study took place at MVJ Medical College and Research Hospital in Bengaluru, Karnataka, India from July 2022 to July 2024. It included a cohort of 125 neonates, all with a gestational age of 28 weeks or older, who were admitted to the Neonatal Intensive Care Unit (NICU) due to pulmonary disease and met the defined inclusion and exclusion criteria. The severity of the condition was assessed using SOPI and AaDO2 values. Spearman’s correlation was used to analyse the relationship between SOPI and AaDO2 values. Results: In the present study, the median age of neonates was one day, with an Interquartile Range (IQR) from 1 to 5 days, and there were 86 males and 39 female babies. The study revealed a strong positive correlation between SOPI and AaDO2, with a correlation coefficient of 0.903 (p-value <0.001). Cut-off values for SOPI were established at 1.33 (sensitivity: 99%, specificity: 96.7%), 1.59 (sensitivity: 99%, specificity: 89.8%), and 1.77 (sensitivity: 97.7%, specificity: 67.6%). These thresholds correspond to AaDO2 levels indicative of mild, moderate, and severe respiratory diseases, respectively, and were statistically significant. Conclusion: A positive correlation exists between SOPI and AaDO2, with a Spearman’s correlation coefficient of 0.903 and p-value <0.001, making it a vital non invasive tool for assessing the severity of respiratory distress in neonates and eliminating the need for Arterial Blood Gas (ABG) analysis.